Isolation and characterization of a phenolic derivative (flavonoid) from Crassocephalum crepidioides with antiangiogenic, anti-inflammatory and antioxidant activities (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
A phenolic compound was successfully isolated from the methanolic extract of the aerial parts of Crassocephalum crepidioides. Structural elucidation was carried out using spectroscopic techniques including UV-Vis, IR, mass spectrometry, and nuclear magnetic resonance (NMR). Based on the combined spectral data, the compound was identified as 3-(dimethylamino)-2-hydroxy-5-(3,5,7-trihydroxychroman-2-yl)benzaldehyde. The bioactivity of the isolated compound was evaluated for antiangiogenic, anti-inflammatory, and antioxidant properties. In the shell-less chorioallantoic membrane (CAM) assay, the compound exhibited significant inhibition of angiogenesis. Furthermore, it demonstrated inhibitory activity against phospholipase A₂ enzyme derived from Daboia russelii (Russell’s viper), suggesting potential anti-inflammatory effects. The compound also displayed notable antioxidant activity, supporting its therapeutic potential in conditions associated with oxidative stress and aberrant angiogenesis. These findings warrant further investigation into its pharmacological applications.